EDUKASI GIZI BERBASIS KEARIFAN LOKAL: PEMANFAATAN DAUN KELOR (MORINGA OLEIFERA) SEBAGAI TEH BOOSTER ASI - Lilik Ariyanti; Atur Semartini; Muhammad Sa’ad (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Breast milk (ASI) is the best source of nutrition for infants, providing essential nutrients and energy beneficial to their development. An adequate volume of breast milk is a key factor in the success of exclusive breastfeeding. Moringa leaves have the potential to increase ASI production by enhancing prolactin levels and supplying vital nutrients. Moringa is one of the natural ingredients cultivated by the Women's Farmer Group (KWT) Manunggal Sejati in Polokarto and can be used to support household nutrition, particularly for families with toddlers under stunting supervision. Unfortunately, Posyandu (community health post) cadres in Polokarto lack sufficient knowledge on how to process moringa leaves as ASI booster helping mothers prevent stunting. The aim of this initiative was to improve the knowledge and skills of Posyandu cadres regarding the utilization of moringa leaves as an ASI booster. The activities were conducted at the Polokarto Village Hall during June–July 2024. The program was divided into four phases, including education, training on making moringa leaf tea, and monitoring-evaluation. The educational outcomes demonstrated an increase in participants’ knowledge about the use of moringa leaf tea. The average pre-test score of Posyandu cadres was 63.79 increasing to 87.24 in the post-test following the training. The significant improvement in post-test scores indicates the effectiveness of the training in enhancing cadres' knowledge. Training Posyandu cadres is a vital step toward improving child health within the community.